Adsorption kinetic models: Physical meanings, applications, and solving methods - Wang, Jianlong; Guo, Xuan (Journal of hazardous materials, 2020)
[Display omitted] •Adsorption empirical kinetic models and mass transfer kinetic models were reviewed.•The physical meanings and applications of 16 adsorption kinetic models were analyzed.•The model validity evaluation equations were summarized based on literature.•A user interface for solving kinetic models was developed based on Excel software. Adsorption technology has been widely applied in water and wastewater treatment, due to its low cost and high efficiency. The adsorption kinetic models have been used to evaluate the performance of the adsorbent and to investigate the adsorption mass transfer mechanisms. However, the physical meanings and the solving methods of the kinetic models have not been well established. The proper interpretation of the physical meanings and the standard solving methods for the adsorption kinetic models are very important for the applications of the kinetic models. This paper mainly focused on the physical meanings, applications, as well as the solving methods of 16 adsorption kinetic models. Firstly, the mathematical derivations, physical meanings and applications of the adsorption reaction models, the empirical models, the diffusion models, and the models for adsorption onto active sites were analyzed and discussed in detail. Secondly, the model validity evaluation equations were summarized based on literature. Thirdly, a convenient user interface (UI) for solving the kinetic models was developed based on Excel software and provided in supplementary information, which is helpful for readers to simulate the adsorption kinetic process.